2021
DOI: 10.1002/lt.26047
|View full text |Cite
|
Sign up to set email alerts
|

Post–Liver Transplant Early Allograft Dysfunction Modifies the Effect of Pre–Liver Transplant Renal Dysfunction on Post–Liver Transplant Survival

Abstract: Pre-liver transplantation (LT) renal dysfunction is associated with poor post-LT survival. We studied whether early allograft dysfunction (EAD) modifies this association. Data on 2,856 primary LT recipients who received a transplant between 1998 and 2018 were retrospectively reviewed. Patients who died within the first post-LT week or received multiorgan transplants and previous LT recipients were excluded. EAD was defined as (1) total bilirubin ≥ 10 mg/dL on postoperative day (POD) 7, (2) international normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Seral creatinine is the most commonly used indicator of kidney function for estimated glomerular ltration rate (eGFR) by evaluating the endogenous creatinine clearance [8]. Previous studies have focused on the effects of recipients' pre-and posttransplant renal dysfunction with increased seral creatinine on the survival outcomes [9,10]. In this study, we interestingly found that the seral creatinine of donors was higher in patients with EAD after DCD liver transplantation.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Seral creatinine is the most commonly used indicator of kidney function for estimated glomerular ltration rate (eGFR) by evaluating the endogenous creatinine clearance [8]. Previous studies have focused on the effects of recipients' pre-and posttransplant renal dysfunction with increased seral creatinine on the survival outcomes [9,10]. In this study, we interestingly found that the seral creatinine of donors was higher in patients with EAD after DCD liver transplantation.…”
Section: Introductionmentioning
confidence: 72%
“…EAD was a critical condition after liver transplantation, contributing to increased complication rates, and subsequent impaired posttransplant survival. The incidence of EAD ranges from 20-40% in recipients after LT, according to the variant de nition and criteria of EAD [4,12,[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. In this study, we adopted the EAD criteria developed by Olthoff in 2010 [12], which was the most acceptable EAD de nition in MELD era, and de ned by elevation of ALT, AST, INR or bilirubin within 7 days after LT. Undoubtably, recipients diagnosed with EAD had a higher probability of increased post-transplant complications, prolonged intensive care unit stays, delayed discharge, and graft failure [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, the development of chronic kidney disease (CKD) before liver transplant persists as a complicated, multifaceted issue leading to a multitude of adverse outcomes including inferior graft survival, increased infection, increased health care cost, and longer duration of stay [3][4][5][6][7]. Patients with pre-LT CKD suffer increased intraoperative blood loss and haemostatic abnormalities, bearing a 15% increased risk of post-operative mortality [8,9]. Common contributing factors of pre-LT CKD include haemodynamic instability, viral or bacterial infection and excessive use of nephrotoxic drugs, which may lead to prolonged ischaemic or toxic insults to the kidney [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%